THE INCREASING TOURISM VISITS THROUGH TOURISM ATTRACTION AND QUALITY OF EXPERIENCE (STUDY ON TOURISTS VISITING D’DIEULAND TOURISM OBJECTS) - Anggraeni, Rini; Hidayah, Riski Taufik; Zulfikar, Iman; Julianti, Sinta; Yuningsih, Virawanti; Rezgaditya, Steviano (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Covid-19 outbreak has caused the tourism industry, especially the D'Dieuland tourist attraction, to experience a significant decline in the number of tourists, both local and foreign. Efforts to increase tourist visits are urgently needed in order to survive and rise from adversity due to the Covid-19 pandemic. The tourism sector in each region competes with each other to increase tourist attraction and customer satisfaction with the quality of the experience. This study aims to increase tourist visits through tourist attraction and quality of experience. The research method used is a verification method with survey techniques to the population, namely tourist who have visited the D’Dieuland tourist attraction which is represented by 100 respondents. The analytical method used is Spearman Rank correlation, Coefficient of the data is IBM SPSS Statistic ver. 20.0. The results showed that the tourist attraction and the quality of the experiences of 76% and 69% had a positive effect on the interest of tourist to visit the D’Dieuland tourist attraction..